Corticosterone Concentrations Reflect Parental Expenditure in Contrasting Mating Systems of Two Coucal Species - Goymann, Wolfgang; Trappschuh, Monika; Urasa, Felister (Frontiers in Ecology and Evolution, 2017)
The period of parental care can be a demanding life-history stage because parents need to find sufficient resources to feed themselves and their offspring. Often, this is reflected by elevated baseline levels of glucocorticoids – hormones that regulate metabolism and energy allocation. During 10 breeding seasons, we studied plasma corticosterone (the major avian glucocorticoid) concentrations as a physiological correlate of parental expenditure in two closely related coucal species with fundamentally different mating systems: the sex-role reversed black coucal (Centropus grillii) with female competition and male-only care and the socially monogamous and biparental white-browed coucal (C. superciliosus). The two species live in the same habitat and share a similar breeding biology. However, female black coucals aggressively defend a territory and produce many eggs for their various male partners, and male black coucals feed their offspring much more frequently and rest less often than female and male white-browed coucals. These differences were reflected in baseline and stress-induced concentrations of corticosterone: male black coucals had higher baseline and stress-induced corticosterone concentrations when they were feeding young than outside a feeding context, and also the concentrations of female black coucals were higher during the main period of breeding when they defended territories and produced multiple clutches. In contrast, baseline and stress-induced concentrations of corticosterone in female and male white-browed coucals did not differ between periods when they were feeding young and periods without dependent offspring. Paradoxically, on an individual basis feeding effort was negatively related to baseline corticosterone in male black coucals and female white-browed coucals. In conclusion, corticosterone concentrations of coucals reflected differences in competition and parental roles and support the notion that a switch from biparental to uniparental care and an increase in mate competition may come at a physiological and energetic cost.